Measuring the Sustainability of Buffalo Farms and Factors Influencing this Sustainability in Samsun Province of Türkiye - Boz, İsmet and Başarır, Aydın and Kılıç, Osman and Fathelrahman, Eihab and Ulhaq, Shamsheer and Shahbaz, Pomi and Riaz, Mohsin and Baydar, Cevahir Kaynakçı and Degafe, Berhanu (Journal of Buffalo Science, 2026)
Agricultural sustainability contributes to the food supply from national resources and prevents rural people from migrating to urban areas, especially in developing countries. This study seeks to assess the sustainability of buffalo farms and the factors influencing their sustainability, collecting data from a sample of 177 buffalo farmers. First, a sustainability index was developed to measure sustainability and compare large and small farms. The factors affecting sustainability were determined using an ordered probit model. According to the findings, large farmers had higher sustainability than small farmers. The factors affecting sustainability are education level, family size, farming land, land allocated to forage crops, number of buffaloes, membership in farmer organizations, and frequency of contact with extension personnel. The results suggested that to increase sustainability and to manage agricultural resources properly in buffalo farms, the support provided by the state should continue to grow, more awareness studies targeting consumers of buffalo products should be conducted to stimulate market growth, and farmer organizations and extension offices should continue to serve more effectively and actively in the region.